A detailed Description of a new species of the Hoplopleura aitkeni group (Phthiraptera:Anoplura: Hoplopleuridae) parasitic on South American Rodents (Mammalia: Rodentia) in Argentina - Castro, Dolores del Carmen (2007)
Hoplopleura paranaensis sp. nov is described from specimens collected from Deltamys kempi Thomas, 1917, on the Delta del Parana, Buenos Aires Province, Argentina. Detailed descriptions of sexes, the three nymphal instars, external architecture of eggs(by scanning electron microscopy) and sites of ovipositon are provided. Differences from Hoplopleura aitkeni Johnson, 1972 are included. A key and discussion of the distribution of the ten species of the aitkeni-group on their hosts, and their respective geographical ranges in Argentina is also given.